Nucleotide Sequences of RNA Transcribed in Infected Cells and by Escherichia coli RNA Polymerase from a Segment of Simian Virus 40 DNA - Dhar, R. (1974)
The nucleotide sequence of 180 residues of an RNA transcript of DNA of simian virus 40 has been deduced. This sequence adjoins a preferred initiation site for E. coli RNA polymerase. Comparison of this sequence with that of complementary RNA of simian virus 40 from infected cells has shown that this site also adjoins the apparent 3′ terminus of some of the cytoplasmic complementary RNA of simian virus 40.